OP0043 Twenty-Four Weeks of Treatment with a Novel Anti-IL-6 Receptor Nanobody® (ALX-0061) Resulted in 84% ACR20 Improvement and 58% DAS28 Remission in a Phase I/Ii Study in RA. (23rd January 2014) - Holz, J.-B.; Sargentini-Maier, L.; De Bruyn, S.; Gachályi, B.; Udvaros, I.; Rojkovich, B.; Bruk, S.; Sramek, P.; Korkosz, M.; Krause, K.; Schoen, P.; D'Artois, J.; et al.
Abstract : Background: ALX-0061 is a monovalent IL-6R targeting Nanobody. It inhibits signalling via soluble and membrane IL-6R. PK/PD modelling resulted in a condensed study design, combining single ascending dose (SAD), multiple ascending dose (MAD) and clinical proof-of-concept using PK, biomarker and clinical readouts as decision tools. Objectives: MAD: To determine the efficacy and safety of 24 weeks of dosing in patients with RA and to investigate the tolerance, PK, PD and immunogenicity after multiple dosing with ALX-0061. Methods: Multicentre, randomised, double-blind, placebo controlled, dose escalation, Phase I/II study in patients with active RA on stable MTX therapy. MAD: In the first 12 weeks patients received placebo or ALX-0061 IV infusion at 1 or 3 mg/kg Q4W, or 6 mg/kg Q8W. In the second 12 weeks, patients with insufficient EULAR response were allowed to rollover (placebo) or to intensify dosing to enrich the safety and efficacy population. Results: Thirty-seven patients with active RA from 6 sites in CEE started at 1 mg/kg (10 patients), 3 mg/kg (11 patients), 6 mg/kg (10 patients) or placebo (6 patients). 31 patients continued on ALX-0061 in the 2 nd 12 weeks with only 4 changing their dosing regimen and 3 rolling over from placebo. The patients initiated on ALX-0061 had a median duration of disease of 5.7 years, median age of 53 years and median BMI of 26 kg/m 2 and moderate-to-severe disease activity (median DAS28 score 4.7; median VAS patient score 49). ALX-0061 was well tolerated for up to 24 weeks. Clinically relevant neutropenia was absent as well as serious infections. Clinically significant signals in lipids were not observed. No anti-drug antibodies were detected. After 24 weeks of treatment, a total of 18 patients (58%) on ALX-0061 achieved DAS28 remission, of which 8 achieved Boolean remission. All DAS28 components contributed evenly and onset of remission occurred as early as week 2 for certain patients. Clinically meaningful improvements for bone oedema were observed and the global RAMRIS scores showed no worsening after 24 weeks. Conclusions: The use of modelling enabled a rational study design with 3 biologically effective dose levels. In patients with active RA, rapid and strong effects on the IL-6 pathway were observed and associated with a strong clinical response. Clinically significant improvement of disease activity occurred fast and almost 60% of patients achieved state of remission at the end of 24 weeks. The treatment was well tolerated at all doses and the improvement of signs and symptoms was accompanied by a reduction in bone oedema and absence of radiographic disease progression. Disclosure of Interest: J.-B. Holz Shareholder of: Ablynx, Employee of: Ablynx, L. Sargentini-Maier Shareholder of: Ablynx, Employee of: Ablynx, S. De Bruyn Shareholder of: Ablynx, Employee of: Ablynx, B. Gachályi: None Declared, I. Udvaros: None Declared, B. Rojkovich: None Declared, S. Bruk: None Declared, P. Sramek: None Declared, M. Korkosz: None Declared, K. Krause: None Declared, P. Schoen Shareholder of: Ablynx, Employee of: Ablynx, J. D'Artois Shareholder of: Ablynx, Employee of: Ablynx, K. Verschueren Shareholder of: Ablynx, Employee of: Ablynx, W. Willems Shareholder of: Ablynx, Employee of: Ablynx, K. De Swert Shareholder of: Ablynx, Employee of: Ablynx, G. Arold: None Declared